Assessment management system for centralized grade reporting / Aqilah Yahaya - Yahaya, Aqilah (Faculty of Computer and Mathematical Sciences, 2007)
The World Wide Web (WWW) has become a powerful tool for global information dissemination. Besides globally distributing documents, the WWW is also utihzed for internal communications. Many universities choose to develop their own environments although commercial solutions for online course management exist. The Information Technology and Science Quantitative (FTMSK) School of MARA University of Technology has developed such an environment. However, the process of sending the students' marks to the Coordinator is still done manually which requires the lecturer to fill in the LI5 form. This project describes a prototype system on Assessment Management System (AMS) that was designed and implemented by the authors as a solution to conventional method. The objective is to develop a dynamic web-based that allows the lecturer to customize their own template based on their inputs. The researcher uses the System Development Life Cycle model to develop this system. This application was written in PHP programming language and MySQL database using the Apache Server, Macromedia Dreamweaver 8 and phpMyAdmin Database Administrator which is the open source software. It is hoped that from this project, it can reduce the lecturer burden as well as eliminate the used of papers.